Flight Behavior of Individual Aerial Insectivores Revealed by Novel Altitudinal Dataloggers - Dreelin, R. Andrew; Shipley, J. Ryan; Winkler, David W. (Frontiers in Ecology and Evolution, 2018)
Swallows and martins (Aves: Hirundinidae) are well-studied with respect to their breeding biology, but major aspects of their individual aerial movement behavior and ecology are poorly understood. Atmospheric conditions can strongly influence both the availability and distribution of flying insects that aerial insectivores rely upon. Because aerial insects are often found in distinct clusters within the aerosphere, we wanted to explore whether aerial insectivore flight altitudes were species-specific and if they were associated with atmospheric conditions. We examined these questions with novel tag technology, an altitude datalogger, on breeding populations of Purple Martin (Progne subis), Tree Swallow (Tachycineta bicolor), and Barn Swallow (Hirundo rustica) in upstate New York during the summer of 2016, providing individual-level flight data on a per minute basis. Using mixed models, we investigated differences in flight altitudes between individuals, species, and varying atmospheric conditions. The major findings were that individuals of each species spent significantly different proportions of their time throughout the day in different aerial strata. In addition, higher flying species such as Purple Martins and Tree Swallows responded positively to greater thermal uplift whereas this predictor had no effect on Barn Swallow flight altitudes. Finally, the differing relationships for all species between their flight altitudes and weather variables suggest that each species may use different atmospheric cues for tracking their environment and/or prey. More research spanning greater time scales and a wider range of atmospheric conditions is needed to determine these relationships in finer detail. We encourage broader use of this or similar methodologies to better understand the behavior and ecology of aerial insectivores globally.